Laparoscopic Resection of a Left Upper Quadrant Mass Leading to a Surprise Diagnosis - Hugo J. R. Bonatti; Reinhardt O. Sahmel; Rodrigo B. Erlich (Case Reports in Surgery)
Background. Resplenectomy is most commonly done for the treatment of recurrent idiopathic thrombocytopenic purpura (ITP) refractory to medical management due to the regrowth of a missed accessory spleen. Case Report. A 66-year-old male had undergone open splenectomy for traumatic rupture 40 years ago. He presented with a leiomyosarcoma of his leg, which was surgically removed. When he developed metastatic disease, chemotherapy was started. He developed left upper quadrant pain, and on CT scan, a 5 cm mass compatible with a sarcoma was found between the tail of the pancreas and the left adrenal gland. During laparoscopy, dense adhesion of the omentum to the abdominal wall and the stomach from his previous splenectomy was divided. The lesser sac was opened through the gastrocolic ligament, and the splenic flexure was taken down. Superior and dorsal to the tail of the pancreas next to the left adrenal gland, the mass was identified and carefully dissected out. The vascular pedicle, which originated from a side branch of the splenic vessels at the tail of the pancreas, was stapled. The gastric fundus showed multiple nodules, and therefore, a modified sleeve gastrectomy was done; also, a 2 cm nodule in segment 5 of the liver and an omental nodule were removed. The tumors and gastrectomy specimen were placed in an endobag and removed through a periumbilical mini-incision. The patient recovered without any complications from the procedure and his LUQ pain resolved. Pathology revealed no sarcoma metastases but accessory spleens in all specimens. Discussion. Splenosis with multiple implants within the abdomen after splenectomy for trauma is a rare condition. In our patient, this seems to have been triggered by chemotherapy for his sarcoma resulting in extramedullary hemopoiesis. Laparoscopic removal of accessory spleens can be safely done.